HAK REPARASI KORBAN KEJAHATAN PENGATURAN DAN IMPLEMENTASI - Anjari, Warih (E-Journal Widya Yustisia, 2017)
In fact the victim is an integral part of the criminal justice system. Normatively victim has not been recognized position as an integral part of the criminal justice system. Reparation of victims of crime can not be directly implemented. In order to be able to implemented through other mechanisms, so that the implementation is very minimal. The purpose of this paper are: (1) to investigate the crime victims reparation setting and (2) to analyze its implementation. The approach used is the legislation and case-based approach, the analysis is done by applying qualitative analysis with the data collection through literature. It can be concluded that: (1) the crime victim’s reparation arrangements scattered in various laws, and (2) its implementation is still very low due to various constraints. The suggestions are that (1) it’s necessary to increase the awareness reparation rights, (2) to the synchronization rights regulations reparation, and Integration reparation rights of victims in the criminal justice system.